Tipping the scales: short-term interventions and counterinsurgency. Issue 4 (1st October 2016) - Cline, Lawrence E.
ABSTRACT: Particularly in African operations, United Nations (UN) peacekeeping forces have faced significant problems in restoring stability. In at least a few situations, unilateral national military interventions have been launched in the same countries. In the cases of Sierra Leone and Côte d'Ivoire, the British and French interventions respectively played a significant role in re-establishing stability. Lessons from these operations suggest that if effective coordination and liaison channels are established, such hybrid unilateral-UN missions can in fact be more successful than "pure" peace operations.